2020
DOI: 10.3390/microorganisms8091401
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: A Dietary Factor to Modulate the Gut Microbiome, Host Immune System, and Gut–Brain Interaction

Abstract: Various benefits of probiotics to the host have been shown in numerous human clinical trials. These organisms have been proposed to act by improving the balance of the gut microbiota and enhancing the production of short-chain fatty acids, as well as by interacting with host cells in the gastrointestinal tract, including immune cells, nerve cells, and endocrine cells. Although the stimulation of host cells by probiotics and subsequent signaling have been explained by in vitro experiments and animal studies, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 149 publications
(196 reference statements)
0
29
0
Order By: Relevance
“…Maternal separation caused disruption of the gut microbiota, and a significant decrease in lactobacilli, in infant rhesus monkeys [ 22 ]; and the exaggerated stress response of the hypothalamic–pituitary–adrenal axis in GF mice was suppressed by reconstitution with Bifidobacterium infantis [ 5 ]. In line with the idea of maintaining psychological homeostasis via the gut–brain axis, several human trials have been performed to evaluate the function of probiotics containing lactobacilli and bifidobacterial strains, in controlling anxiety and depression [ 23 , 24 ]. However, there remains limited evidence for the efficacy of probiotics in treating mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal separation caused disruption of the gut microbiota, and a significant decrease in lactobacilli, in infant rhesus monkeys [ 22 ]; and the exaggerated stress response of the hypothalamic–pituitary–adrenal axis in GF mice was suppressed by reconstitution with Bifidobacterium infantis [ 5 ]. In line with the idea of maintaining psychological homeostasis via the gut–brain axis, several human trials have been performed to evaluate the function of probiotics containing lactobacilli and bifidobacterial strains, in controlling anxiety and depression [ 23 , 24 ]. However, there remains limited evidence for the efficacy of probiotics in treating mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Postulating that the microbiome could influence endometriosis development is logical. The benefit of probiotics in prevention and treatment of gastrointestinal as well as extraintestinal disorders [38][39][40] is now established.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that various bene ts of probiotics to the host have been shown in numerous human clinical trials, the role of these organisms is to improve the balance of the intestinal ora and increase the production of short-chain fatty acids(SCFAs), which can directly or indirectly play the role of anti-in ammatory, protect the intestinal barrier function, regulate human metabolism and immunity [39][40][41]. Especially, (SCFAs) play an important role in the treatment of obesity, insulin resistance, diabetes and other metabolic diseases [42].As well as study showed that SCFAs can improve intestinal health by promoting the increase of intestinal barrier function and reducing the translocation of bacterial endotoxins on the intestinal wall, this is one of the reasons it reduces in ammation and improves insulin resistance [43].…”
Section: Discussionmentioning
confidence: 99%